Strategi Pemberdayaan Komunitas Melalui Urban Farming dalam Mewujudkan Kemandirian Pangan: Studi Kasus di Pradah Kalikendal Surabaya - Nihlatul Falasifah; Sumiati (CV Omah Kreaor, 2025)
Rapid urbanization in Indonesia poses serious challenges to urban food security. This study examines a program to revitalize hydroponic urban farming in RW 04 Pradah Kalikendal, Surabaya, which had previously failed. The purpose of this study is to analyze how participatory community empowerment strategies can effectively revive this initiative and contribute to local food security. The method used is a qualitative case study with a Participatory Action Research (PAR) approach. This approach actively involves residents in all stages of the program, from problem identification to evaluation. The results show that the participatory approach has succeeded in transforming past failures into collective learning. The empowerment strategy focused on improving technical capacity and collective organization. Summary data showed that social innovations such as the establishment of a daily “duty roster” significantly increased community participation, sense of ownership, and social capital. This program has had a multidimensional impact, including strengthening social bonds, reducing household food expenditures, and increasing access to healthy vegetables. It is concluded that the sustainability of urban farming in dense environments does not only depend on technology, but is fundamentally determined by the success of the empowerment process. The scientific contribution of this research is the confirmation that a participatory empowerment model that transforms failure into collective learning through practical social innovation is the key to revitalizing community programs that have failed due to previous top-down approaches.